APOBEC3B Activity Is Prevalent in Urothelial Carcinoma Cells and Only Slightly Affected by LINE-1 Expression - Jaguva Vasudevan, Ananda Ayyappan; Kreimer, Ulrike; Schulz, Wolfgang A.; Krikoni, Aikaterini; Schumann, Gerald G.; Häussinger, Dieter; Münk, Carsten; Goering, Wolfgang (Frontiers in Microbiology, 2018)
The most common mutational signature in urinary bladder urothelial carcinoma (UC) is assumed to be caused by the misdirected activity of APOBEC3 (A3) cytidine deaminases, especially A3A or A3B, which are known to normally restrict the propagation of exogenous viruses and endogenous retroelements such as LINE-1 (L1). The involvement of A3 proteins in urothelial carcinogenesis is unexpected because, to date, UC is thought to be caused by chemical carcinogens rather than viral activity. Therefore, we explored the relationship between A3 expression and L1 activity, which is generally upregulated in UC. We found that UC cell lines highly express A3B and in some cases A3G, but not A3A, and exhibit corresponding cytidine deamination activity in vitro. While we observed evidence suggesting that L1 expression has weak positive effect on A3B and A3G expression and A3B promoter activity, neither efficient siRNA-mediated knockdown nor overexpression of functional L1 elements affected catalytic activity of A3 proteins consistently. However, L1 knockdown diminished proliferation of a UC cell line exhibiting robust endogenous L1 expression, but had little impact on a cell line with low L1 expression levels. Our results indicate that UC cells express A3B at levels exceeding A3A levels by far, making A3B the prime candidate for causing genomic mutations. Our data provide evidence that L1 activation constitutes only a minor and negligible factor involved in induction or upregulation of endogenous A3 expression in UC.